Strategi Pembelajaran Berbasis Multiple Intelligences pada Mata Pelajaran Fiqih Kelas VII di MTs Hubbulwathan Kecamatan Mandau, Kabupaten Bengkalis Riau - Nurbaiti, Intan; Ilmi, Darul (Lembaga Yasin AlSys, 2023)
The background of this research is that problems were found in the implementation of learning strategies based on multiple intelligences carried out by Fiqh teachers. Based on the results of the pre-observation, it was found that many Fiqh teachers still found students who were less active in the learning process, even though the teacher had implemented a learning strategy based on multiple intelligences. The purpose of this research is to describe the implementation of learning strategies based on multiple intelligences in class VII Fiqh subjects at MTs Hubbulwathan, Mandau subdistrict, Bengkalis district, Riau. To find out the supporting and inhibiting factors in the implementation of learning strategies based on multiple intelligences in class VII Fiqh subjects at MTs Hubbulwathan, Mandau sub-district, Bengkalis district, Riau. This study uses a type of field research (field research) with a qualitative descriptive approach. This research was conducted at MTs Hubbulwathan, Mandau sub-district, Bengkalis district, Riau. The informants in this study were Fiqh teachers and class VII students. Data collection techniques in this study were observation, interviews and documentation. Based on the results of the research that the authors have done, the results show that: learning strategies based on multiple intelligences implemented by Fiqh teachers are using tests, observing student activities inside and outside the classroom, collecting and understanding student documentation data and planning the learning process. In the implementation carried out by Fiqh teachers, the intelligence developed is linguistic intelligence, bodily-kinestic intelligence, interpersonal intelligence, intrapersonal intelligence. In its implementation students are facilitated by methods that are in accordance with student intelligence. So it can be concluded that of the five implementations of the learning strategies used by Fiqh teachers in class only fulfill two points of implementation, this is the reason why Fiqh teachers still find students not active in the learning process. Supporting factors for the implementation of learning strategies based on multiple intelligences are facilities and infrastructure that are almost complete so as to support the learning process using learning strategies based on multiple intelligences. The inhibiting factors for the implementation of learning strategies based on multiple intelligences are the lack of learning time and incomplete facilities.